The experience of sensorimotor integration of a lower limb sensory neuroprosthesis: A qualitative case study - Schmitt, Melissa S.; Wright, John D.; Triolo, Ronald J.; Charkhkar, Hamid; Graczyk, Emily L. (Frontiers in Human Neuroscience, 2023)
Lower limb prosthesis users often struggle to navigate uneven terrain or ambulate in low light conditions where it can be challenging to rely on visual cues for balance and walking. Sensory feedback about foot-floor interactions may allow users to reduce reliance on secondary sensory cues and improve confidence and speed when navigating difficult terrain. Our group has developed a Sensory Neuroprosthesis (SNP) to restore sensation to people with lower limb amputation by pairing electrical stimulation of nerves in the residual limb applied via implanted neurotechnology with pressure sensors in the insole of a standard prosthesis. Stimulation applied to the nerves evoked sensations perceived as originating on the missing leg and foot. This qualitative case study reports on the experiences of a 68-year-old with a unilateral trans-tibial amputation who autonomously used the SNP at home for 31 weeks. Interview data collected throughout the study period was analyzed using a grounded theory approach with constant comparative methods to understand his experience with this novel technology and its impacts on his daily life. A conceptual model was developed that explained the experience of integrating SNP-provided sensory feedback into his body and motor plans. The model described the requirements of integration, which were a combination of a low level of mental focus and low stimulation levels. While higher levels of stimulation and focus could result in distinct sensory percepts and various phantom limb experiences, optimal integration was associated with SNP-evoked sensation that was not readily perceivable. Successful sensorimotor integration of the SNP resulted in improvements to locomotion, a return to a more normal state, an enhancement of perceived prosthesis utility, and a positive outlook on the experience. These outcomes emerged over the course of the nearly 8 month study, suggesting that findings from long-term home studies of SNPs may differ from those of short-term in-laboratory tests. Our findings on the experience of sensorimotor integration of the SNP have implications for the optimal training of SNP users and the future deployment of clinical SNP systems for long-term home use.